From New Mexico State University - From New Mexico State University (Issues in Science and Technology Librarianship)
The Southwest Center for Codes and Standards was recently established at the New Mexico State University Library. The feebased service center provides access to over one million national and international standards, including military specifications and standards, and state, county, and municipal technical codes.